2002
DOI: 10.1046/j.1365-2133.2002.04782.x
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of atopic dermatitis in school entrants is associated with individual life-style factors but not with local environmental factors in Hannover, Germany

Abstract: In conclusion, we confirm an association between a privileged life-style and a higher incidence of AD in a large number of investigated children between 5 and 9 years of age (97.6% of children were 6 or 7 years old) for the German city of Hannover. We propose the socio-economic status as a marker for different life-styles and social micro-environments in further studies as there were multiple significant correlations between individual social and environmental factors. The macro-environment seems to be less im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
2
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 34 publications
4
15
2
5
Order By: Relevance
“…In Korea, according to Lee et al, as monthly income and education status increase, there was more severe atopic dermatitis populations observed [42]. Also, Werner et al and Snijders et al reported the relationship between a privileged life-style and an increased incidence of AD [43], [44]. Therefore, there are relationship among socioeconomic status, educational level, and city size with prevalence of atopic dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…In Korea, according to Lee et al, as monthly income and education status increase, there was more severe atopic dermatitis populations observed [42]. Also, Werner et al and Snijders et al reported the relationship between a privileged life-style and an increased incidence of AD [43], [44]. Therefore, there are relationship among socioeconomic status, educational level, and city size with prevalence of atopic dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…The close relationship between food allergy and childhood AD indicated the potentially similar immunological mechanisms which deserves further investigation [26]. Living in urban areas indicate a more westernized life style and diet, with less exposure to farms or rural areas, and could lead to more use of chemicals [27]; these factors have been demonstrated to be associated with atopic diseases in children in other studies as well [3,21]. …”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed a strong association between parental social class and children's incidence of AD with increasing frequency in privileged classes [29]. It was suggested that cross-infections in early childhood between siblings in large, underprivileged families may play a protective role for the manifestation of AD, and conversely, children of privileged social classes are much more likely to suffer from AD [30].…”
Section: Discussionmentioning
confidence: 99%